2008
DOI: 10.1021/ef800088c
|View full text |Cite
|
Sign up to set email alerts
|

Associative π−π Interactions of Condensed Aromatic Compounds with Vanadyl or Nickel Porphyrin Complexes Are Not Observed in the Organic Phase

Abstract: Association of vanadium and nickel petroporphyrin compounds with aromatic groups is commonly invoked as an important mechanism for aggregation of asphaltenes. In this study, the interaction of vanadium and nickel octaethylporphyrin with condensed aromatic compounds and bridged aromatic compounds was investigated. Neither UV-vis nor fluorescence spectroscopy detect any interactions between porphyrins and aromatic ring groups in either the ground or excited states. The lack of detectable binding of these model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…Dickie and Yen were the first who proposed an aggregation scheme for the macrostructure of petroleum asphaltenes, within which petroporphyrins could stack to the aromatic sheets of asphaltene [24]. Their opinion as well as the abilities of EPR techniques to shed light on aggregation structure was criticized by authors of [64]. In [64], solutions of porphyrin complexes (i.e., model systems) were investigated by UV-Vis and fluorescence spectroscopy.…”
Section: Geofluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dickie and Yen were the first who proposed an aggregation scheme for the macrostructure of petroleum asphaltenes, within which petroporphyrins could stack to the aromatic sheets of asphaltene [24]. Their opinion as well as the abilities of EPR techniques to shed light on aggregation structure was criticized by authors of [64]. In [64], solutions of porphyrin complexes (i.e., model systems) were investigated by UV-Vis and fluorescence spectroscopy.…”
Section: Geofluidsmentioning
confidence: 99%
“…Their opinion as well as the abilities of EPR techniques to shed light on aggregation structure was criticized by authors of [64]. In [64], solutions of porphyrin complexes (i.e., model systems) were investigated by UV-Vis and fluorescence spectroscopy. From the lack of detectable binding of these model compounds, it was suggested that the association of the majority of vanadium and nickel petroporphyrins in crude oils with the asphaltene fraction may be due to other functionalities appended to the porphyrin ring, rather than favorable π − π stacking interactions of aromatic rings with the porphyrin core itself.…”
Section: Geofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and synthesis of complex organic molecules to validate, compare, and illuminate molecular characteristics of the asphaltenes is both time‐consuming and expensive. Thus, more often than not, researchers rely on commercially available metalloporphyrins (e.g., Ni II ‐ and V IV O derivatives of octaethyl‐ and tetraphenylporphyrin) as simplified probes for intermolecular aggregation, often coupled with the use UV/Vis and fluorescence spectroscopy to monitor the process . Unfortunately, the limited range of commercial porphyrin compounds in turn limits, and even biases, analytical results and conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more often than not, researchers rely on commercially available metalloporphyrins (e.g.,N i II -a nd V IV Od erivatives of octaethyl-a nd tetraphenylporphyrin)a ss implified probesf or intermolecular aggregation,o ften coupled with the use UV/Vis and fluorescences pectroscopy to monitor the process. [26] Unfortunately,t he limited range of commercialp orphyrin compounds in turn limits,a nd even biases, analytical resultsa nd conclusions. As ar esult,w eh ave workedt od evelop efficient protocols for the synthesis of larger and more diverses tructural representatives of the asphaltenes.…”
Section: Introductionmentioning
confidence: 99%